THE EXAMPLES OF AXIS - ORDER FUNCTIONAL THINKING IN THE WORKS OF ZOLTÁN KODÁLY - ORDASI, Péter (Studia Universitatis Babes-Bolyai Musica, 2010)
The functional axis-order in Bartók’s works, as the final consequence of the tempered ton system was discovered by Ernő Lendvai from the fifties of the twentieth century. We can find the axis-order functional thinking in the works of Zoltán Kodály, as an important element of his personal style, but that is mostly undiscovered, especially in connection with the Hungarian folksongs. The study Heptatonia secunda by Lajos Bárdos gives new ideas and tools for the analysis of Kodály’s oeuvre. Several characteristic examples are collected in this article from songs, choral works and instrumental music by Kodály to prove that idea, and, looking for the origin of the axis-order it shows its somehow earlier appearance in the music of Vivaldi, Haendel and Mozart.